Electricity market crisis in Europe and cross border price effects: A quantile return connectedness analysis - Do HX; Nepal R; Pham SD; Jamasb T (Elsevier B V, 2024)
As the interconnection of the European electricity markets and integration of renewables progresses, there is little known about interconnectedness across them at times of market turbulence. The electricity crisis of 2021 and 2023 were significant events that can also provide lessons in the behaviour of integrated markets with high renewables under stress. Despite the impacts of the COVID-19 pandemic and the Russia-Ukraine war on the European energy market, little is known about their effects on the transmission of risks between the electricity markets. We employ the quantile connectedness approach to quantify the return connectedness between eleven key European markets, as well as the natural gas and carbon markets. We then examine the effect of the two crises on the interconnectedness. We find significant return interconnectedness, driven by spillover effects, among the markets. Analysis of connectedness across quantiles shows that the spillover effects are much stronger at tail ends of conditional distribution. Moreover, our results reveal opposite effects from crises on market interconnectedness. While the COVID-19 pandemic reduced the interconnectedness, the Russia-Ukraine war intensified the return shock transmission. Finally, we find that the natural gas and carbon markets are net recipients of return shocks across the quantiles.
Keywords: Natural gas; European emission allowance; Electricity markets; COVID-19; Russia-Ukraine war; Quantile connectedness